A Study of the Relationship between Mining and the Performing Arts in Australia 1850 – 1914: case studies of the Ballarat and Kalgoorlie-Boulder goldfields. - Latchford, Norma (Curtin University, 2020)
In describing the historical development of these two settlements based on mining, this thesis outlines the ways in which the performing arts played a significant role in the evolving social and cultural development of both centres and that mining, especially in the form of the these two goldrushes, was highly influential in the distinctive development of the performing arts in Australia in the second half of the nineteenth century and beyond.